Perceived Utilization of Dental and Oral Health Services at RSGM UNIMUS Based on the Level of Education - Retno Kusniati; Emilia Nurul Sholekah (Universitas Muhammadiyah Yogyakarta, 2021)
Utilization of dental and oral health services characterized by interaction between patients who need health services and health care workers. The level of utilization of health services is very important since it could be an indicator of the occurrence of a type of health service the level of public awareness of dental and oral health. The level of utilization of dental and oral health services can be measured by the patient's perception of the services provided. An objective of this study was to investigate the relationship between levels of education and the perceived utilization of dental and oral health services at RSGM Unimus Semarang, Central Java. The project used an accidental sampling method with 76 subjects were recruited from RSGM Unimus Semarang. This research was conducted using a questionnaire designed to measure the factors of utilization of dental and oral health services. The results of the research using chisquare analysis showed that there was no significant relationship between the level of education (p = 0.089) and utilization of dental and oral health services at RSGM Unimus. Interestingly, respondents with a higher level of education had higher frequencies to utilize facilities at RSGM Unimus compared to respondents with lower level education.